Fabrication of ultra-shallow boron junctions using proximity rapid thermal diffusion - Nolan, Martina (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2000)
This work presents proximity rapid thermal diffusion (RTD) as a technique for fabricating shallow p-type junctions for LDD devices. Boron-doped spin-on dopant (SOD) is used as a dopant source in proximity RTD. Fourier transform infrared (FTIR) spectroscopy and spectroscopic ellipsometry are initially used to analyse and optimise the SOD dopant source. Bare and oxidised silicon wafers are doped using the optimised SOD dopant source. The boron junctions are analysed using SIMS and the four-point probe technique. Boron diffusion coefficients are evaluated from the SIMS profiles using Boltzmann-Matano analysis. Proximity RTD is used to fabricate p-n junction diodes. The diodes exhibit excellent current-voltage (IV) characteristics, with near ideal forward characteristics, low leakage currents and sharp avalanche breakdown voltages. Micro-Raman spectroscopy (MRS), synchrotron X-ray topography (SXRT) and optical microscopy are used to determine the thermal stress and the boron-induced strain that is generated in wafers during rapid thermal oxidation (RTO) and rapid thermal diffusion. The thermal stress deteriorates with time at the peak temperature. The introduction of boron also generates extra strain in the lattice. However, the stress that is generated for very short process times is minimal and does not degrade device performance. Finally, a LDD process that is compatible with proximity RTD is proposed.
Keywords: Electrical and Electronic Engineering, Ph.D.; Ph.D. Trinity College Dublin